A General One‐Pot Strategy for the Synthesis of High‐Performance Transparent‐Conducting‐Oxide Nanocrystal Inks for All‐Solution‐Processed Devices1. Issue 2 (17th November 2014) - Song, Jizhong; Kulinich, Sergei A.; Li, Jianhai; Liu, Yanli; Zeng, Haibo
Abstract For all‐solution‐processed (ASP) devices, transparent conducting oxide (TCO) nanocrystal (NC) inks are anticipated as the next‐generation electrodes to replace both those synthesized by sputtering techniques and those consisting of rare metals, but a universal and one‐pot method to prepare these inks is still lacking. A universal one‐pot strategy is now described; through simply heating a mixture of metal–organic precursors a wide range of TCO NC inks, which can be assembled into high‐performance electrodes for use in ASP optoelectronics, were synthesized. This method can be used for various oxide NC inks with yields as high as 10 g. The formed NCs are of high crystallinity, uniform morphology, monodispersity, and high ink stability and feature effective doping. Therefore, the inks can be readily assembled into films with a surface roughness of 1.6 nm. Typically, a sheet resistance of 110 Ω sq−1 can be achieved with a transmittance of 88 %, which is the best performance for TCO NC ink‐based electrodes described to date. These electrodes can thus drive a polymer light‐emitting diode (PLED) with a luminance of 2200 cd m−2 at 100 mA cm−2.